Imaging findings for 2-[18F]fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography in blastic plasmacytoid dendritic cell neoplasm: case series and literature review - Zhou, Yujing; Li, Kaiyue; Jin, Xin; Yuan, Lujie; Zhou, Hang; Li, Xin (Frontiers in Medicine, 2025)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare hematologic malignancy with a poor prognosis. The value of 2-[18F]fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography (18F-FDG PET/CT) in BPDCN has not been clarified. This study aimed to investigate the imaging findings of 18F-FDG PET/CT in patients with BPDCN based on cases from our institution and the literature. The clinical and radiological data were obtained from five patients with BPDCN from our institution between March 2014 and July 2023. Additionally, we complemented our dataset with 13 cases derived from the studies published in English to ascertain the potential efficacy of 18F-FDG PET/CT scan in identifying this malignancy. Information collected included age, sex, extent of lesion involvement, biopsy site, karyotype, immunophenotype, treatment, prognosis, and 18F-FDG PET/CT-features. A total of 18 cases of BPDCN featuring PET/CT manifestations were assessed. We observed considerably increased 18F-FDG uptake in lesions of all 18 cases [maximum standardized uptake value (SUVmax), 9.1; range, 1.5–9.1]. The positive findings of 18F-FDG PET/CT mainly included skin (11/18), lymph nodes (9/18), bone (4/18), and spleen (2/18). Except for these organs, abnormal 18F-FDG uptake lesions were detected in the lung and breast. The roles of 18F-FDG PET/CT in our study were initial staging (18/18), selection of biopsy site (5/18), and treatment evaluation (7/18). Prognostic data were available in 16 patients. The median overall survival (OS) in this cohort was 12.0 months, and the median follow-up time was 10.0 months. Among these, 10 cases reported SUVmax of lesions at the same time. Five out of eight patients with SUVmax > 2.5 died within 2 months of diagnosis, whereas two other cases with SUVmax < 2.5 survived within 10 and 34 months of follow-up. The data from our case series and those from the literature demonstrated the potential utility of 18F-FDG PET/CT in diagnosis, staging, prognosis, and treatment follow-up of BPDCN. Early identification of this rare malignancy on imaging can expedite diagnosis and facilitate early treatment.